FINANCIAL MANAGEMENT ANALYSIS: THE ROLE OF MANAGEMENT ACCOUNTING INFORMATION SYSTEMS WITH ENVIRONMENTAL UNCERTAINTY AS A MODERATING VARIABLE - januri, januri; Firza Alpi, M (International Journal of Economic, Technology and Social Sciences (Injects), 2025)
Based on the research results, it was concluded that the Management Accounting Information System has a positive and significant influence on Financial Management Performance in Hospitals throughout Medan City, meaning that whenThe company increases the implementation of a good Management Accounting Information System, it will improve Financial Management Performance, System, Environmental Uncertainty has a positive and significant effect in moderating the influence of the Management Accounting Information System on Financial Management Performance in Hospitals throughout Medan City, meaning that when the company increases the provision of compensation plus the implementation of good Environmental Uncertainty, it will improve Financial Management Performance and Environmental Uncertainty has a positive and significant effect in moderating.